Subjective Expectations for Health Service Use and Consequences for Health Insurance Behavior - Nathan Kettlewell (Institute of Labor Economics (IZA), 2020)
I evaluate the accuracy of people's subjective probability expectations for using various health services. Subjective expectations closely reflect patterns of observed utilization, are predicted by the same covariates as observed utilization, and correlate with objective measures of risk. At the same time, observable characteristics like age and health are weakly predictive of service demand. Through a series of examples, I demonstrate how subjective expectations can provide new insights about health behavior, specifically in the areas of asymmetric information, moral hazard and estimating welfare attributable to private care. The findings support collecting subjective expectations about health services in household surveys for use in applied research.
Keywords: D82; D84; I11; I12; I13; 330; subjective expectations; beliefs; subjective probabilities; health insurance; healthcare demand